The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1302/0301-620x.92b5.22849
|View full text |Cite
|
Sign up to set email alerts
|

Proximal humeral fractures with a severe varus deformity treated by fixation with a locking plate

Abstract: We treated 47 patients with a mean age of 57 years (22 to 88) who had a proximal humeral fracture in which there was a severe varus deformity, using a standard operative protocol of anatomical reduction, fixation with a locking plate and supplementation by structural allografts in unstable fractures. The functional and radiological outcomes were reviewed. At two years after operation the median Constant score was 86 points and the median Disabilities of the Arm, Shoulder and Hand score 17 points. Seven of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 23 publications
0
43
2
1
Order By: Relevance
“…The restoration of medial mechanical support of the fractures is an important factor that is emphasized for a successful clinical outcome in proximal humeral fractures. 14,24,25) Gardner et al 14) showed that when there is an unstable medial mechanical support by comminuted fractures at the proximal humerus, the positioning of the locking screws on the lower side of the humeral head along the humeral calcar is critical. In this study, we also highlighted that patients who showed contact of the medial humerus with the cortical bone or mechanical support of the medial humerus by the locking screws located on the humeral calcar had a greater Constant score, less change in humeral neck-shaft angle, and less change in humeral head height.…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of medial mechanical support of the fractures is an important factor that is emphasized for a successful clinical outcome in proximal humeral fractures. 14,24,25) Gardner et al 14) showed that when there is an unstable medial mechanical support by comminuted fractures at the proximal humerus, the positioning of the locking screws on the lower side of the humeral head along the humeral calcar is critical. In this study, we also highlighted that patients who showed contact of the medial humerus with the cortical bone or mechanical support of the medial humerus by the locking screws located on the humeral calcar had a greater Constant score, less change in humeral neck-shaft angle, and less change in humeral head height.…”
Section: Discussionmentioning
confidence: 99%
“…A lateral plate can then be used to correct the translation of the medial shaft and reduce and fix the fragments into the anatomic position [7,24]. In cases where there is a significant metaphyseal bone defect, the defect may be filled with local bone graft or bone-graft substitute [25]. Alternatively, an allograft strut may be used to support the medial column, especially in cases of varus instability [26].…”
Section: Open Reduction and Internal Fixationmentioning
confidence: 99%
“…There have been several recent studies which have demonstrated satisfactory outcomes following ORIF of proximal humeral fractures [25,[27][28][29][30][31][32]. Brunner et al [27] treated 158 fractures and at 1 year follow up noted a Constant score of 72.…”
Section: Open Reduction and Internal Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…7) Unreduced or poorly reduced fractures with varus angulation of the neck-shaft angle can be a cause of avascular necrosis of the head of humerus. [8][9][10] Nevertheless, the indications for selecting a specific treatment from the wide variety of available procedures like wires, sutures, intra-medullary nails and other fixation techniques 3) have all been used to maintain the fracture reduction. However, the ability of these fixations alone to restore anatomical relationships, maintain stability and prevent avascular necrosis to the humeral head remains controversial.…”
Section: Introductionmentioning
confidence: 99%